2021
DOI: 10.3390/brainsci11040434
|View full text |Cite
|
Sign up to set email alerts
|

Not Only Mania or Depression: Mixed States/Mixed Features in Paediatric Bipolar Disorders

Abstract: Background: early onset is frequent in Bipolar Disorders (BDs), and it is characterised by the occurrence of mixed states (or mixed features). In this systematic review, we aimed to confirm and extend these observations by providing the prevalence rates of mixed states/features and data on associated clinical, pharmacological and psychopathological features. Methods: following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, we searched from inception to 9 February 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…This findings is in line with previous research (Wozniak et al, 2004). So far, many studies have suggested that illness onset in pediatric bipolar patients have a less common presentation with “the classical” euphoria-like symptoms and is more often characterized by irritability, polarity shifts, and mixed symptoms (Goldstein & Birmaher, 2012; Janiri et al, 2021). In our population, BD patients were 1.7 times more likely to exhibit a first major depressive episode with mixed features than UD patients (BD/UD ratio = 1.70, p = .037, Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…This findings is in line with previous research (Wozniak et al, 2004). So far, many studies have suggested that illness onset in pediatric bipolar patients have a less common presentation with “the classical” euphoria-like symptoms and is more often characterized by irritability, polarity shifts, and mixed symptoms (Goldstein & Birmaher, 2012; Janiri et al, 2021). In our population, BD patients were 1.7 times more likely to exhibit a first major depressive episode with mixed features than UD patients (BD/UD ratio = 1.70, p = .037, Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of “decreased need for sleep” (YMRS item 4) symptom, “difficulty with sleep” (CDRS-R item 4) may assess simple insomnia and seems to be associated primarily with a depressive symptom cluster. In contrast, reduced sleep symptoms in bipolar depression youth with manic or hypomanic features may be a by-product of influences of hyperactivity and irritability that characterize the manic state in youth, and who may commonly present with co-occurring attention deficit with hyperactivity [ 2 , 31 ]. Sleep disturbance as a “bridge” symptom may therefore be a useful marker of mixed states [ 8 , 14 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The co-occurrence of depressive and manic symptoms in the same mood episode presents significant challenges for the diagnosis and treatment of people with bipolar disorder. The presence of subthreshold hypomanic symptoms in pediatric bipolar depression may be associated with significant impairment in functioning, and can complicate the illness course and treatment outcome [ 1 , 2 ]. Recognizing the importance of mixed states during depressive episodes in characterizing the course of illness and response to treatment in either bipolar or unipolar depression, the Diagnostic and Statistical Manual 5 th edition (DSM-5) added “mixed features” specifiers to episodes of major depression, hypomania or mania.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ] Another meta-analysis of 11 studies that included studies involving pediatric bipolar patients ( n = 1365) reported a pooled prevalence of 55.2% (95% CI: 40.1–70.3) (mostly assessed on Structured Clinical Interview for-DSM-IV TR criteria) and those with mixed states having high rates of comorbidities, mostly Attention Deficit Hyperkinetic Disorder. [ 14 ] When one looks at these meta-analyses, it is evident that most of the data on mixed features as defined by DSM-5 is for patients with BD, with limited data on patients with depression. Further, the studies that evaluated the prevalence of mixed features in patients with depression have not specified whether this has been studied in patients with first-episode depression (FED) or recurrent depressive disorder.…”
Section: Introductionmentioning
confidence: 99%